Private Landowners’ Relation to Land and Forest in Two Estonian Counties - Jörgensen, Hans; Grubbström, Ann; Stjernström, Olof (Journal of Northern Studies, 2011)
This comparative study is based on two large surveys of private land and forest owners in two Estonian counties. While more than half of Põlvamaa is covered with forests, Läänemaa has a potential for summer tourism and second homes. We explore different rationales for obtaining landed property and analyse the individual property holders’ relations to—and use of—land and forests. Based on the two interlinked restitution and privatisation processes from 1991 onwards, our surveys reveal two main rationales among the owners: emotional and economic. The owners’ relations to the property are connected with legacies from both the interwar independence and the Soviet period. In addition, different rationalities, ambitions and attitudes are also related to how the property was obtained. In spite of the demand for land, many resituated landowners have chosen to maintain or recreate family property, even if the property was not actively used. In both Põlvamaa and Läänemaa the emotional bonds to land are strong among the owners of restituted or inherited property, while this is a weaker factor among those who have obtained land or forest through privatisation.